Underweight and overweight in primary school children in eThekwini district in KwaZulu-Natal, South Africa - Threethambal Puckree; Pooveshni Naidoo; Prabashni Pillay; Therona Naidoo (AOSIS, 2011)
Background: The prevalence of overweight and obesity in children has been increasing worldwide. South Africa has minimal data on childhood body weight. Objectives: This study determined whether school children in the eThekwini district in KwaZulu-Natal, South Africa, were underweight or overweight. Method: A survey with quantitative and qualitative components was conducted amongst 120 participants between 10 years and 12 years of age. The participants were randomly selected from six public schools in an urban district of the province. A calibrated Goldline bathroom scale was used to measure body weight and a KDS Freo non-elastic measuring tape was used to measure height. A questionnaire consisting of open and close-ended questions collected demographic and lifestyle information. Body mass index (BMI) was calculated from height and weight data. Proportions of obese, overweight and underweight children were calculated and subjected to chi-square tests at the p ≤ 0.05 significance level. All qualitative information was summarised. Results: According to World Health Organization criteria, 66% of the children were underweight, 28% were of normal weight and 5% were overweight. The proportion of underweight children increased with age (64% of children aged between 10 years and 11 years vs 70% for 12-year-olds). Of the underweight children, 41% were female and 51% were Indian.Only one child was obese. BMI was related to dietary patterns and activity levels during and outside school hours. Conclusion: A significant number of primary school children from the six selected public schools in the eThekwini district were underweight. More effort is required to improve the nutritional status of school children in the eThekwini district.